IMPLEMENTASI PENDIDIKAN KARAKTER DALAM PENGEMBANGAN ASPEK AFEKTIF SISWA PADA PEMBELAJARAN EKONOMI BERMODELKAN DARING KELAS X IPS DI SMA SANTUN UNTAN - Nadila, Ria; Sulistyarini, Sulistyarini; Witarsa, Witarsa (Jurnal Kajian Pembelajaran dan Keilmuan, 2022)
ABSTRACT : The purpose of this study was to find out the followings: 1) the profile of character education during the Economics learning process with an online model of class X Social Sciences at SMA Santun UNTAN (Universitas Tanjungpura), 2) students' affective aspects in economic learning with an online model of class X social science at SMA Santun UNTAN, 3) implementation in developing character values in learning Economics with an online class X IPS model at SMA Santun UNTAN. This research used qualitative research. The researcher interviewed teacher and observed students"™ activity during the Economics class. The results of this study were that students were exposed with the values of religion, honesty, disciplinary values, independence, and responsible character.Keywords : Implementation of character education